Trust: an essential component in nursing crisis leadership; a hybrid concept analysis - Karin Hugelius (BMC Nursing)
Abstract Background Given the increasing trend of disasters, terrorist attacks, pandemics and other crises, crisis leadership is crucial for nurses who lead others and for those working in such situations. There is a need to define and explore the concept of trust as a component of crisis leadership in nursing. This concept analysis aimed to explore the concept of trust in crisis leadership from a nursing perspective. Methods A hybrid concept analysis was conducted. The method consisted of three phases: (I) a theoretical phase relying on a structured literature search, including 11 scientific publications; (II) a field-work phase, in which qualitative thematic analysis of interviews with 30 nurses who had been deployed and/or had led others during crises, was conducted and (III) a final analytic phase, where the results from these data collections were merged. Results The analysis suggested that the fundamentals of trust included a perceived intention to do good, the capabilities of both the leader and the team and the perceived predictability of the leader’s behaviour. Trust was found to be built on a perceived forward-looking direction, self-trust and the personal attributes of the leader, such as ethical conduct, the ability to predict the development of crises and an intention to take responsibility and be honest. The social attributes of the relationship between the leader and the team included the intention not to leave anyone behind, loyalty and fostering a sense of belonging among team members. The organisational attributes included a clear organisational structure and clarity of mandate. Conclusions Trust is an essential component of crisis leadership that depends on a leader’s perceived intention to do good, predictability of the leader’s behaviour and the capabilities of both the leader and the team. The development of trust relies on the personal attributes of the leader, the social relationship between the leader and the team and organisational attributes. Nurses appointed to lead others during a crisis need to understand the fundamentals of trust as part of leadership in highly demanding situations. Thus, it can be argued that being a leader in a crisis situation requires distinct personal and professional attributes and skills compared to those used to meet routine demands.